(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article examines the effective use of financial management methods in companies as a vital driver of sustainable growth, profitability, and organizational resilience. In an increasingly complex and competitive economic environment, companies must adopt integrated financial strategies that support both short-term performance and long-term value creation. The study highlights key financial management methods, including budgeting and forecasting, cost control, capital budgeting, working capital optimization, and financial risk assessment. Emphasis is placed on the role of data analytics, digital technologies, and performance-based evaluation systems in enhancing financial decision-making and accountability. The research incorporates comparative analysis of industry practices and empirical evidence from companies operating in both developed and emerging markets. Findings indicate that companies which systematically apply modern financial management tools achieve better financial stability, improved resource allocation, and stronger investor confidence. The article concludes by proposing a comprehensive framework for the strategic and adaptive application of financial management methods to increase overall corporate efficiency and competitiveness.